2017
DOI: 10.1038/s41467-017-01953-y
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocytic expression of human sodium-taurocholate cotransporting polypeptide enables hepatitis B virus infection of macaques

Abstract: Hepatitis B virus (HBV) is a major global health concern, and the development of curative therapeutics is urgently needed. Such efforts are impeded by the lack of a physiologically relevant, pre-clinical animal model of HBV infection. Here, we report that expression of the HBV entry receptor, human sodium-taurocholate cotransporting polypeptide (hNTCP), on macaque primary hepatocytes facilitates HBV infection in vitro, where all replicative intermediates including covalently closed circular DNA (cccDNA) are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 47 publications
(54 reference statements)
3
73
1
Order By: Relevance
“…HBV was purified and concentrated from HepAD38 cell culture supernatant using previously published protocols 27,62 . In brief, cells were cultivated in multi-layer flasks and supernatant collected every 3-4 days.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…HBV was purified and concentrated from HepAD38 cell culture supernatant using previously published protocols 27,62 . In brief, cells were cultivated in multi-layer flasks and supernatant collected every 3-4 days.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…To date, hepadnaviruses have been found in multiple Hominoids, including chimpanzees and orangutans (38). On the other hand, no HBV or hepadnavirus infections have been reported in Old-World monkeys, even though this family is the closest to the Hominoids (Figure 1) [Although a unique case of HBV genotype D infection was reported in Macaca fascicularis (cynomolgus macaques) from Mauritius (39), another recent paper showed that this macaques exhibited no evidence of current or prior HBV infection (29)]. Since Old-World monkeys are the closest species to human that are regarded to be non-susceptible to HBV or hepadnaviruses, we focused on these two lineages for the comparison among NTCP genes.…”
Section: Resultsmentioning
confidence: 99%
“…The sodium taurocholate cotransporting polypeptide [NTCP, also designated as solute carrier family 10A1 (SLC10A1)] was recently identified as a host factor that functions as an HBV entry receptor; NTCP, which originally was characterized as a hepatic transporter for the uptake of bile acids by hepatocytes, binds to the HBV envelope protein, notably to the preS1 region, thereby mediating viral entry into the host (26). NTCP has been suggested to be a key determinant of the species-specificity of HBV, as primary monkey hepatocytes can support the replication of intracellular HBV but not the entry of the virus into host cells (27), and complementation the monkey cells with human NTCP (hNTCP) permits HBV entry and thereby the whole infection cycle both in cell culture and in vivo (28, 29). These results indicate that the inability of monkey Ntcp to support HBV infection serves as the species barrier preventing HBV infection in monkey.…”
Section: Introductionmentioning
confidence: 99%
“…(11) However, attempts to replicate those findings were unsuccessful. (12) When we initially isolated WMHBV, we examined spider monkeys as surrogate hosts, since woolly monkeys are endangered. In that study, maximum viral titers of 10 5 GE/mL were obtained with viremia that lasted only six weeks.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent attempt to replicate infection of Mauritian cynomolgus macaques with that strain of HBV was unsuccessful. (12) In 1998, a hepatitis B-like virus was isolated from zoo-housed woolly monkeys suffering from fulminant hepatitis (WMHBV), (13) and an infectious clone of the virus was reported in 2003. (14) WMHBV is a hepadnavirus with the same genetic organization as human HBV.…”
mentioning
confidence: 99%